Detection chain and electronic readout of the QUBIC instrument - Stankowiak, G; Piat, M; Battistelli, ES; Azzoni, S; Et al. (Society of Photo-Optical Instrumentation Engineers, 2020)
The Q and U Bolometric Interferometer for Cosmology (QUBIC) Technical Demonstrator (TD) aiming to shows the feasibility of the combination of interferometry and bolometric detection. The electronic readout system is based on an array of 128 NbSi Transition Edge Sensors cooled at 350mK readout with 128 SQUIDs at 1K controlled and amplified by an Application Specific Integrated Circuit at 40K. This readout design allows a 128:1 Time Domain Multiplexing. We report the design and the performance of the detection chain in this paper. The technological demonstrator unwent a campaign of test in the lab. Evaluation of the QUBIC bolometers and readout electronics includes the measurement of I-V curves, time constant and the Noise Equivalent Power. Currently the mean Noise Equivalent Power is ~ 2 x 10-16W= p √Hz